Early Stunting Prevention for Youth Groups in Jabung Sisir Village, Paiton District: Early Stunting Prevention for Youth Groups in Jabung Sisir Village, Paiton District - Nadhiroh, Anis Yusrotun; Mistria, Mistria Harmonis (Universitas Nahdlatul Ulama Surabaya, 2025)
Stunting is a serious public health issue that affects child development and the quality of future generations. Preventing stunting should not only start during pregnancy but also in adolescence, especially among teenage girls as future mothers. This program aims to raise awareness among adolescents in Jabung Sisir Village, Paiton Sub-district, about the importance of balanced nutrition, reproductive health, and readiness for healthy parenthood. The methods applied include nutrition education, group discussions, basic health checks, and training on healthy life skills. The results show an increase in adolescents’ knowledge and awareness regarding early stunting prevention. This program is expected to foster a generation that is more conscious about maintaining health from adolescence as an early step to break the cycle of stunting in the future.